Extending the Predictive Mind. - Clark, Andy (Australasian Journal of Philosophy, 2024)
How do intelligent agents spawn and exploit integrated processing regimes spanning brain, body, and world? The answer may lie in the ability of the biological brain to select actions and policies in the light of counterfactual predictions—predictions about what kinds of futures will result if such-and-such actions are launched. Appeals to the minimization of 'counterfactual prediction errors' (the ones that would result under various scenarios) already play a leading role in attempts to apply the basic toolkit of the neurocomputational theory known as 'predictive processing' to higher cognitive functions such as policy selection and planning. In this paper, I show that this also leads naturally to the discovery and use of extended processing regimes defined across heterogeneous mixtures of biological and non-biological resources. This solves a long-standing puzzle concerning the 'recruitment' of the right non-neural processing resources at the right time. It reveals how (and why) human brains spawn and maintain extended human minds.